The Role of Tehranian Citizens' Participation in Realization «Tobacco-Free Tehran Programme» - Kobra Kharaghani; Karam Habibpour ghatabi; Badri Barandeghi (Iranian Association of Health Education and Health Promotion, 2020)
Background and Objective: «Tobacco-Free Tehran Programme» was implemented by the Municipality of Tehran with the aim of creating a city-free by building awareness and sensitivity to the dangers of tobacco use. The researcher has analyzed the role of Tehranian citizens' participation in the realization of the «Tobacco-Free Tehran Programme».   Materials and Methods: The present has been conducted by survey method and questionnaire technique among 384 persons of citizens participating in tobacco control prevention programs in a tobacco-free week in 22 districts of Tehran municipality by convenience sampling method.   Results: Findings showed that 14.8% had complete knowledge about Tehran city without tobacco plan, 30.7% had sporadic information about this plan and 41.9% had no information about it. The results of the one-sample t-test showed that the level of citizen's knowledge and participation in the «Tobacco-Free Tehran Programme» was low. Also, participation rate of non-smokers, women, older age groups and married people was higher than the others, but the participation of different educational and occupational groups was the same.   Conclusion: Findings implies that Tobacco-Free Tehran Programme has failed to achieve its intended objectives in the past few years in the field of tobacco control, and one of the main reasons for this has been the lack or weakness of public participation.